Analysis of Plasticizer Contamination Throughout Olive Oil Production - Flávia Freitas; João Brinco; Maria João Cabrita; Marco Gomes da Silva (Molecules)
This study monitored the contamination of 32 plasticizers in olive oil throughout the production and storage process. Samples were collected at different stages of production from three olive oil production lines in distinct regions of Portugal and analyzed for 23 phthalates and 9 phthalates substitutes to identify contamination sources. The developed analytical method employed liquid–liquid extraction with hexane/methanol (1:4, v/v), followed by centrifugation, extract removal, and freezing as a clean-up step. Analysis was conducted using gas chromatography tandem mass spectrometry (GC-MS/MS), with detection limits ranging from 0.001 to 0.103 mg/kg. The results revealed that plasticizer concentrations progressively increased at each stage of the production process, although unprocessed olives also contained contaminants. Di-isononyl phthalate (DINP) was the most prevalent compound, but all phthalates regulated by the European Union for food contact materials were detected, as well as some unregulated plasticizers. In a few packaged olive oils, DINP concentrations exceeded the specific migration limits established by European regulations. Samples stored in glass and plastic bottles showed no significant differences in plasticizer concentrations after six months of storage. However, higher concentrations were observed in plastic-packaged samples after 18 months of storage. Our findings indicate that the primary source of plasticizer contamination in olive oil originates from the production process itself, except for prolonged storage in plastic bottles, which should be avoided.